IDENTIFIKASI TANAH TERCEMAR LINDI TEMPAT PEMBUANGAN AKHIR SAMPAH MUARA FAJAR DENGAN METODE GEOLISTRIK - Darmayanti, Lita; Yusa, Muhamad; RA, Esther (Bumi Lestari; Vol 11 No 2 (2011), 2011)
The purpose of this study was to identify soil contamination by leachate from a landfill (TPA) using geoelectric method. Leachate is the liquid waste arising from the introduction of external water into the garbage heap, dissolve, and rinse the dissolved materials, including organic materials are also the result of biological decomposition process. Leachate contained heavy metals and many other organic pollutants that can contaminate soil and groundwater. Geoelectric method is one of the geophysical methods that exploit the variation of resistivity based on the measurement of potential differences caused by electrical currents injected into the earth. The study began by examining the landfill soil type, then check its resistivity with level of leachate varied, ranging 0-100%, in the laboratory. Furthermore, resistivity measurements in the field to determine the spread of leachate. In addition, examination of pollutant content in the leachate was done. The result showed the soil type of landfill was high plasticity clay (CH). Resistivity value of soil with varies level of leachate was 13.5 to 30 Î©m. On the field, it found value of resistivity soil ranged from 13.5 to 30 Î©m has spread along the 37 m to the east with an average depth of 0 to 1.60 m and 29 m to the south with an average depth of 0 to 1.85 m.
Keywords: geoelectric method, leachate, resistivity